(untitled) (Prosiding SEMDIKJAR (Seminar Nasional Pendidikan dan Pembelajaran), 2025)
This research is motivated by the learning process that has problems in terms of the use of Learning Media. In learning, teachers only use lecture methods, media, and facilities that do not support learning, especially in Natural Science material. The impact is that students do not understand the learning material, especially low student learning outcomes. So the researcher developed learning media for the material Classifying Animals Based on Their Food Types so that teachers and students can conduct learning and access the material at any time. This study aims to determine the validity, practicality and effectiveness of the module used. This study uses the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). The conclusions from the results of this study are (1) Taman Satwa Media gets an average value of 87.5%, meaning that the learning media is very valid for use without revision. (2) Taman Satwa Media is stated to be very practical to use and gets an average value of 90.1%. (3) Taman Satwa Media is stated to be very effective and gets an average value from students of 93.5%.